Leveraging Transformative Digitalization Strategies to Enhance Learning at Mountains of the Moon University, Uganda - Kisembo, Maliko; Balimutajjo, Sudi; Kagambe, Edmond; Kasiita, Tawheed; Namubiru, Aisha; Kang’ahi, Maurine (East African Journal of Education Studies, 2025)
Mountains of the Moon University (MMU) is transitioning from traditional to modern educational practices to better meet the demands of the digital era. This study explored the implementation of digitalization strategies at MMU, aiming to bridge gaps between conventional methods and technological innovations. A qualitative approach was employed, utilizing semi-structured interviews and focus group discussions with 37 participants, including faculty members, student leaders, and administrative staff. Thematic analysis revealed that while MMU's digitalization efforts, including Learning Management Systems (LMS), online collaboration tools, a technical support desk, and regular blended learning schedules, have facilitated course delivery and virtual discussions, significant challenges remain. Issues such as low internet connectivity, insufficient ICT skills among users, and high data costs continue to impede effective implementation. Despite these barriers, digital tools have positively impacted student engagement and performance. The study recommends enhancing internet infrastructure, boosting digital literacy through targeted training programs, fostering a culture of digital innovation, innovative pedagogical initiatives and expanding blended instruction. Addressing these challenges can help MMU evolve into a dynamic, technology-driven institution, ensuring high-quality education that meets the needs of the digital age